Pengaruh Kepemimpinan Transaksional Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Mediasi Pada Variasi Mobil di Kota Jambi - Muhammad Irfansyah; Zulfina Adriani; Nur Hasanah (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This research was conducted to obtain an overview of the influence of transactional leadership on employee performance through job satisfaction as a mediating variable in car variations in Jambi City and to find out whether there is a mediating role of job satisfaction on the influence of leadership on employee performance. This type of research is quantitative. The data collection technique uses Structural equation modeling (SEM) with the SmartPLS program. The results show that transactional leadership and job satisfaction have a significant influence on employee performance, and job satisfaction has a mediating role.